Effects of Escherichia coli Nissle 1917 on immunity, blood constituents, antioxidant capacity, egg quality and performance in laying Japanese quail - Asghar Sedaghat; Mohammad Amir Karimi Torshizi; Mohammad Reza Soleimani (Poultry Science)
This study was conducted to evaluate the effects of E.coli Nissle 1917 (EcN) on immune responses, blood parameters, oxidative stress, egg quality, and performance of laying Japanese quail. A total of one-hundred day-old quail chicks were assigned to 1 of 4 treatments based on probiotic concentration: 1 (0 CFU/mL; control), 2 (104 CFU/mL), 3 (106 CFU/mL), and 4 (108 CFU/mL). The average egg production throughout the 8 wks of the laying phase increased with the increase in EcN supplementation (R2= 0.96). The egg production was also significantly different in wk 4, 7, and 8 of the laying phase with the control group demonstrating the poorest performance. External egg quality parameters, including shell strength, Roche index, albumen height, yolk weight, shell weight, shell thickness, and Haugh unit, also showed higher values in groups receiving EcN. Likewise, these groups demonstrated heavier egg weight (EW) and lower MDA in the meat sample. The MDA concentration of fresh yolk samples in groups receiving EcN was higher but diminished after iron-inducing (P < 0.05). No differences were observed in ADFI, FCR, EM, yolk cholesterol and triglyceride, hematocrit, SRBC, NDV, CMI immune responses (DNCB and PHA), H:L ratio, and internal organ weights. Plasma cholesterol and uric acid were the only blood constituents showing higher values in male birds in groups of EcN (P < 0.05); no appreciable differences were observed in the rest of the blood parameters in male birds and none in females. Further, a substantially higher Avian Influenza Virus (AIV) titer resulted from treatments 3 and 4 in male birds among humoral immune responses. These results demonstrated that EcN in the birds’ drinking water could profoundly influence laying performance, egg quality, immune function, and enhanced antioxidant capacity.